A new Afrotropical genus Doggerella gen. nov. of braconine wasp (Hymenoptera: Braconidae) with twelve new species - Mahmood, Khalid; Papp, Jeno; Quicke, Donald L. J. (Zootaxa, 2011)
A new genus Doggerella gen. nov. (Braconinae, Braconidae) is erected to include one previously described and twelve new species predominantly from the southern part of Africa. These species are Doggerella turneri sp. nov. (the type species), D. augustata sp. nov., D. longitergita sp. nov., D. deflexa sp. nov. and D. sulphurea sp. nov. from Republic of South Africa (Cape Province), D. albopilosa (Szépligeti, 1913) comb. nov. from Kenya, D. azhari sp. nov. and D. minuta sp. nov. from Namibia, D. cohaerens sp. nov. from Angola, D. landingi sp. nov. and D. shaheena sp. nov. from Cote d’Ivoire, D. mishkati sp. nov. from Madagascar and D. transversa. sp. nov. from Zimbabwe. Photomicrographs are provided to illustrate morphological characters of the species.